Captain Awesome vs. the sinister substitute teacher - Kirby, Stan (Kirby, Stan. Captain Awesome, 2016)
When a sinister substitute teacher takes over their class, it is up to Eugene and the rest of the Sunnyview Superhero Squad to find Ms. Beasley and foil the sub's plot.